Incidence of lower extremity injury in the National Football League: 2015 to 2018 - Mack, C. D.; Kent, R. W.; Coughlin, M. J.; Shiue, K. Y.; Weiss, L. J.; Jastifer, J. R.; Wojtys, E. M.; Anderson, R. B. (The American Journal of Sports Medicine, 2020)
Background: Lower extremity injuries are the most common injuries in professional sports and carry a high burden to players and teams in the National Football League (NFL). Injury prevention strategies can be refined by a foundational understanding of the occurrence and effect of these injuries on NFL players.